A Socially Constructed Individualist: An Interactionist Study of Role-Making among Orchestral Conductors - Byczkowska-Owczarek, Dominika (Qualitative Sociology Review, 2022)
The paper analyzes the role-making of an orchestral conductor. It is framed by the symbolic interactionist perspective and focuses on Ralph Turner’s role-making theory and the works of Alfred Schütz and Howard S. Becker and associates. The research project is based on grounded theory methodology. The applied techniques include semi-structured interviews, video-elicited interviews, observations of teaching conducting and opera rehearsals, video analysis, and secondary data analysis. The results reveal how the process of role-making is shaped during secondary socialization and indicate the social features of the role, such as high social prestige, awareness of the body, an exclusive social group, and teamwork. The role-making process is based on permanent interactions and negotiations with social actors: the composer and the musical score, the orchestra, soloists, ballet, and the audience. Additionally, it is influenced by cultural factors, such as the conductor’s gender, age, nationality and international experience, competencies, as well as the type of professional contract. At the same time, conductors need to actively maintain the image of determined and resolute individualists, as expected by the social actors they interact with.